Design of a five peak tunnable metasurface for terahertz biological detection with vanadium dioxide - Tingting Yan; Tiantian Guo; Jin Yang (Scientific Reports)
Abstract This paper introduces the design of a five-peak tunnable metasurface unit cell. The unit adopts a three-layer multi-resonant structure to construct five absorption frequencies, and the absorptive and reflective states are controlled by the phase change material vanadium dioxide. The author explains the working principle of the five absorption frequencies generated by the unit cell based on the electrical field diagram of the unit cell. The structure is symmetrical, therefore polarization is insensitive. The scattering pattern of the 10 $$×$$ 10 array constructed by the unit cell between two states is compared in this paper. This design is expected to be applied in terahertz multi-frequency biological sample detection.